2020
DOI: 10.1080/15476286.2020.1817265
|View full text |Cite
|
Sign up to set email alerts
|

Rbm24 regulates inner-ear-specific alternative splicing and is essential for maintaining auditory and motor coordination

Abstract: Tissue-specific alternative splicing (AS) is emerging as one of the most exciting types of mechanisms associated with organ development and disease. In the auditory system, many hearing-related genes undergo AS, and errors in this process result in syndromic or non-syndromic hearing loss. However, little is known about the factors and mechanisms directing AS in the inner ear. In the present study, we identified a novel RNA-binding protein, Rbm24, which was critically involved in regulating inner-earspecific AS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…27 Hence, Rbm24-inducible knockout mouse model was constructed (Figure S1A-D). 28 Tamoxifen (100 mg/kg daily for 5 days) was injected intraperitoneally into 8-week-old CreERT2-Rbm24 loxp/loxp mice (N = 32) to generate Rbm24 conditional knockout mice. Wild type (WT) mice were administrated with the same dose of tamoxifen (Figure 1A).…”
Section: Rbm24-knockout Mice Develop Spontaneous Colorectal Adenomasmentioning
confidence: 99%
“…27 Hence, Rbm24-inducible knockout mouse model was constructed (Figure S1A-D). 28 Tamoxifen (100 mg/kg daily for 5 days) was injected intraperitoneally into 8-week-old CreERT2-Rbm24 loxp/loxp mice (N = 32) to generate Rbm24 conditional knockout mice. Wild type (WT) mice were administrated with the same dose of tamoxifen (Figure 1A).…”
Section: Rbm24-knockout Mice Develop Spontaneous Colorectal Adenomasmentioning
confidence: 99%
“…Rbm24 -/-OHCs, but not IHCs, are degenerated by P19 [37]. RBM24 is also involved in mRNA stability and pre-mRNA alternative splicing of several genes, including Cdh23 and Pcdh15, which are crucial for the development of HC stereocilia [55][56][57]. Our study also revealed that GATA3 expression is decreased and IKZF2 expression is increased in OHCs in the absence of RBM24, which could be a direct or indirect effect of RBM24 loss.…”
Section: Roles Of Rbm24 and Its Regulation During Cochlear Hc Develop...mentioning
confidence: 54%
“…Nevertheless, our previous work revealed that the otic vesicle is largely unaffected in conventional Rbm24a knockout zebrafish, suggesting that RBM24 is not necessary for early inner ear development at least in zebrafish (Zhang et al, 2020). Recently, Zheng and colleagues reported that Tamoxifen‐induced global knockout of Rbm24 in adult mice causes hair cell degeneration, suggesting that RBM24 is necessary for hair cell maintenance mainly through regulating alternative splicing (Zheng, Yuan, et al, 2021). Our present work reveals that RBM24 is also required for hair cell development.…”
Section: Discussionmentioning
confidence: 99%